Analisis isi komunikasi publik polri terkait mudik libur natal dan tahun baru - Rulinawaty, Rulinawaty; Yudhakusuma, Dudi; Hendriarto, Prasetyono; Dila Erlianti; Rini Fitria (Jurnal Komunikasi Profesional, 2022)
The government has decided to cancel the implementation of Community Activity Restrictions (PPKM) Level 3 in all regions, especially the State Civil Apparatus (ASN), during the 2021 Christmas and New Year holidays of 2022. State Civil Apparatuses (ASN) are not allowed to take leave or leave the area during Sunday national holidays, both before and after Christmas and New Year. The purpose of this research is to find out how Polri's public communication is related to the 2021 Christmas and New Year's holiday homecoming for 2022. The method used is Krippendorff content analysis which is carried out through digital observations on the Instagram account of the Indonesian National Police @divisihumaspolri for the period 1 December 2021 to 20 December 2021. The results of this study indicate that public communication carried out by the National Police through Instagram @divisihumaspolri is dominated by messages containing benefits for security and safety during the Christmas and New Year's 2022 holidays during the Covid-19 pandemic.